Ações e controle patrimonial de bens móveis permanentes: um estudo na Universidade Federal de Santa Maria - Rodrigues, Beatriz Corte Real (2024)
Asset management in public institutions faces significant challenges due to the complexity and magnitude of the movable assets involved. In the context of Higher Education Institutions (HEIs), such as the Federal University of Santa Maria (UFSM), issues like inadequate control, underutilization of assets, and difficulties in asset tracking have financial and operational implications, especially in a scenario of budget constraints and increasing demand for transparency and efficiency. This study aimed to analyze how patrimonial control actions for permanent movable assets are developed at UFSM, identifying best practices, challenges, and proposing improvements for asset management. To achieve this objective, a qualitative case study was conducted, combining documentary analysis, semi-structured interviews with asset management personnel, and direct observation. Data analysis was carried out using Bardin's content analysis method, encompassing various academic and administrative units of the institution. The results revealed critical points such as inconsistencies in records, lack of communication between sectors, and underutilization of existing tools. However, best practices related to the training of patrimonial agents and the use of computerized systems were also identified. The diversity of realities among UFSM’s units highlighted specific challenges, particularly for centers managing larger volumes of assets. As practical contributions, the study provides guidelines for optimizing patrimonial control processes, promoting greater efficiency and rational use of public resources. Theoretically, the research enriches the debate on governance and asset management in public universities, emphasizing the importance of efficient control as an instrument of accountability and transparency.